Religiosidade e sentimento de solidão em idosos - Costa, Fernanda Vial (2012)
Introduction: Widowhood is a special situation, unplanned, which provokes sadness, feeling of loneliness and adapt to new roles. In this sense religiosity can be a coping strategy to overcome these difficulties. Objective: verify the association between the feeling of loneliness and religiosity within elderly widowers. Method: cross-sectional and quantitative study with a sample of 200 elderly widowers aged ≥ 60 years who attend the clinics of the Institute of Geriatrics and Gerontology of PUCRS. The instruments used were the University of California, Los Angeles loneliness scale and the Scale of Frequency of Religious Practices and the Scale of Intrinsic/Extrinsic Religiousness. Results: The loneliness level of the sample was considered high having reached an average 48,4±4,6. For the estimation of the scale of solitude, the results indicated that (36.7%) of the variations occurred in scale score of solitude can be explained by income, for, the higher the income the higher the level of solitude. Still it was found significance in the correlation between loneliness and sex, for it came out that widowers demonstrate greater social satisfaction than widows. Most elderly presented tendency to intrinsic religiosity 25,5±7,3. Another significant relationship was found between religiosity and the age range of participants, being that the older the person, the greater the tendency for the practice of intrinsic religiosity. Significant difference was found only in the relationship between the scale of loneliness and social religiosity scale. Conclusion: As a general overview it was found that income is a predictive factor for the feeling of loneliness and the age range is a predictive factor for the practice of intrinsic religiosity among elderly widows. Furthermore, the practice of social religiosity can decrease the feeling of loneliness of the elderly widowers